The relationship between analysis of upper limb function, physical activity, and neck pain in wood carvers - Ni Nyoman Ryanti Wijayani; Ni Luh Putu Gita Karunia Saraswati; Ni Luh Nopi Adnyani; Ni Komang Ayu Juni Antari (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Indonesia has a large workforce and frequent work accidents. The work of woodcarving artisans in Ubud village has a high risk of accidents. Neck pain is a common problem these artisans face due to static movements, vibrations, and excessive physical activity. Ergonomics in the work environment is the key to preventing pain and fatigue, but non-ergonomic working positions often occur in wood artisans. Therefore, this study aims to explore the relationship between rapid upper limb assessment (RULA) analysis, physical activity, and complaints of neck pain among woodcarvers. Methods: This type of research is an analytic observational with a cross-sectional design. The sampling technique is total sampling. The number of subjects obtained is 31 people according to predetermined criteria. The instruments used were the International Physical Activity Questionnaire (IPAQ) questionnaire to measure physical activity levels, the RULA form to assess work position, and the Numeric Rating Scale (NRS) questionnaire to measure complaints of neck pain. This study used two techniques, namely univariate and bivariate analysis, using the SPSS program. Results: Based on bivariate analysis using Spearman’s rho non-parametric method on 31 respondents, a significant correlation was found between RULA analysis and complaints of neck pain with a correlation coefficient of 0.55 and also found that there is a significant relationship between physical activity and complaints of neck pain with a correlation coefficient of 0.83. Conclusion: There is a relationship between RULA analysis and complaints of neck pain in woodcarving craftsmen in Ubud Village and there is a relationship between physical activity and complaints of neck pain in complaints of neck pain in woodcarving craftsmen in Ubud Village.